Provocations on Media Architecture - Callender, Ian; Dell'Aria, Annie (S.l. : Set Margins' publications, 2023)
Ijeoma, Ekene ; Yang, Hoa ; Daily tous les jours ; Saloojee, Ozayr ; Barns, Sarah ; Bloch, Stefano ; Brush, Brian W. ; de Waal, Martijn ; Rapati, Tiemen ; Audry, Sofian ; Foyer, Anthea ; Li, Jiabao ; Nish-Lapidus, Matt ; Tobin, Ana ; Blight, Susan ; Cayley, John ; The Current Team ; Dobbin, Sherry ; Rodgers, Scott ; Weisling, Anna
boek